Tandem mass tag-based quantitative proteomics analyses of a chicken-original virulent and its attenuated Histomonas meleagridis strain in China - Chen, Qiao-Guang; Zhang, Yu-Ming; Chen, Chen; Wang, Shuang; Li, Zai-Fan; Hou, Zhao-Feng; Liu, Dan-Dan; Tao, Jian-Ping; Xu, Jin-Jun (Frontiers in Veterinary Science, 2023)
Histomonas meleagridis can cause histomonosis in poultry. Due to the prohibition of effective drugs, the prevention and treatment of the disease requires new strategies. Questions about its pathogenic mechanisms and virulence factors remain puzzling. To address some of these issues, comparative proteomic analysis of TMT was performed on a virulent strain and its attenuated strain of Chinese chicken-origin . A total of 3494 proteins were identified in the experiment, of which 745 proteins were differentially expressed (fold change ≥1.2 or ≤0.8 and p＜0.05 ), 192 were up-regulated in virulent strain, and 553 were up-regulated in attenuated strain. Gene ontology (GO) analysis revealed that the differentially expressed proteins were mainly involved in organic material metabolic processes, primary metabolic processes and cellular metabolic processes, exerting protein binding functions, and most were distributed in the cytoplasm and organelle. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that these differentially expressed proteins were mainly involved in pathway of Spliceosome, Cytosolic DNA-sensing pathway, Ribosome biogenesis in eukaryotes, RNA transport and Ribosome. In addition, some differentially expressed proteins were quantified by parallel reverse monitoring (PRM) assay to verify the results of TMT analysis. The above results provide some candidate protein-coding genes for further functional verification, which will help to understand the molecular mechanism of pathogenicity and attenuation of H. meleagridis more comprehensively.